Educação em Ciências e Cultura Indígena: os fenômenos naturais na concepção dos alunos da comunidade Ñandeva-Guarani da reserva Porto Lindo – Japorã/MS. - Couto , Cristiane Beatriz Dahmer (2022)
Assuming that each community develops its specific knowledge and that the way these are perceived can influence the relationships that individuals build with each other, the objective of this research was to describe the traditional indigenous knowledge of the members of the Ñandéva-Guarani community, identifying the conceptions that are presented at school in Science teaching and their implications for the construction of intercultural relationships at school and in their daily lives. The topics listed for dialogue with the discipline of Science are: the emergence of life on earth, rain, thunder, the phases of the moon, characteristics transmitted from parents to children, the formation of sex (male or female) and disability. in the human being. Also present in this work are themes such as traditional indigenous culture and the most striking conflicts and/or changes that systematized education has been harming and/or contributing to indigenous people from generation to generation. The research was carried out at the Indigenous Municipal School of Early Childhood Education and Elementary Education Mbo'ehao Tekoha Guarani Polo in Japorã/MS, with a qualitative approach. The literature review was based on books, articles, dissertations and theses. The document analysis analyzed the Federal Constitution of 1988, in the Law of Directives and Bases of National Education 9394/96, in the Guidelines for Indigenous School Education and other pertinent legislation. The methodology, in oral history, outlined moments for data collection such as: script elaboration, recorded interview, transcription, textualization, interpretation and archiving. Students, teachers, parents, and the chief of Reserva Porto Lindo were interviewed. The studies pointed to the dialogue between the different knowledge, all, in a way, maintained a dialogue with the culture, in a more or less intense way, with a tendency to return to the cultural tradition to the detriment of scientific knowledge. We aim with this research, in addition to disseminating the knowledge and reflections that we come across, to instigate and stimulate the academic community to direct research also towards indigenous peoples.